2021
DOI: 10.3390/ijerph182010786
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Perceived Importance of a Novel Emergency Food Program during COVID-19 and Program Recipient Characteristics

Abstract: Following rising unemployment rates and consequent loss of income due to COVID-19, many people have been seeking meal assistance. This study examines the impact of a community-based free meal distribution program during the pandemic in Kentucky, reviewing characteristics of recipients of the program. Demographics, health behaviors, food insecure classification, and rating of importance of the meal program were collected. Qualitative feedback on the impact of the program was collected via open response. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 14 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Full details of the study designs, settings, populations, and domains of food security examined are summarized in Table 2 . More than half of the 22 included studies were conducted in rural USA ( n = 13) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], with others being conducted in Australia [ 39 , 40 ], Canada [ 41 ], the UK [ 42 ], Poland [ 43 ], Israel [ 44 ], Chile [ 45 ] and Germany [ 46 ]. One study was conducted in an international sample, comprising participants from 62 different countries [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Full details of the study designs, settings, populations, and domains of food security examined are summarized in Table 2 . More than half of the 22 included studies were conducted in rural USA ( n = 13) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], with others being conducted in Australia [ 39 , 40 ], Canada [ 41 ], the UK [ 42 ], Poland [ 43 ], Israel [ 44 ], Chile [ 45 ] and Germany [ 46 ]. One study was conducted in an international sample, comprising participants from 62 different countries [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study was conducted in an international sample, comprising participants from 62 different countries [ 47 ]. Most studies ( n = 16) collected data on adult populations or household-level information [ 27 , 29 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 ], while two specifically focused on households or families comprising both adults and children [ 26 , 32 ]. Three studies reported on the impact of COVID-19 on food outlets such as stores [ 28 ], farmers markets [ 33 ], and food banks [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations